Formulasi Sirup dan Aktivitas Antelmintik Infusa Daun Kelor (Moringa oleifera) terhadap Cacing Ascaridia galli Schrank Secara In Vitro - Nur Ismiyati (Politeknik Kesehatan Bhakti Setya Indonesia, 2019)
Worm infection is common infection in Indonesia. Worm infection can be treated using traditional medicine such as Moringa leaf (Moringa oleifera). The aim of this research is to know whether Moringa oleifera leaves infusion has anthelmintic activity of Ascaridia galli Schrank and to determine LC50 and LC90 values. This research design used 3 groups, NaCl 0,9 % solution as negative control, piperazine citrate 0.4% solution as positive control, and Moringa oleifera leaves infusion concentration solution 10% b/v, 20% b/v, 40% b/v. Each treatment group consisted of 25 worms divided into 5 petri. Observation of worm mortality was carried out every 2 hour for 48 hours. The data obtained were analyzed using the One-way ANOVA test and followed by the Mann Whitney test. The formulation of Moringa leaf infusion syrup was made in 20 % and 40 % concentrations, then tested for stability. The result calculation based on linear regression showed that LC50 Moringa oleifera leaves infusion at concentration 23,61% and LC90 at concentration 82,36%. The result showed the sig p 0.00 < 0.05 means that there were significant differences between treatment groups and times of worm mortality. The quality test result of Moringa leaf infusion syrup showed that the best formulation is 20 % concentration. The conclusion of the study showed that the Moringa oleifera leaves infusion can be formulatied in syrup and has anthelmintic activity against Ascaridia galli Schrank worms in vitro.